2017
DOI: 10.1093/ndt/gfx305
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin concentration and the risk of hemorrhagic and ischemic stroke in patients undergoing hemodialysis: the Q-cohort study

Abstract: Our results suggest that low hemoglobin concentrations are associated with a high risk of hemorrhagic stroke, but not of ischemic stroke, in patients undergoing hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
1
17
0
2
Order By: Relevance
“…Compared with previous cross-sectional studies of anemia prevalence in CKD, we observed higher proportions of severe CKD patients experiencing grade 2 or 3 anemia at any given point of time, likely due to the longitudinal nature of our study enabling us to identify incident anemia events. Our results corroborate earlier findings on the association between anemia and clinical outcomes in smaller and selected populations from the United States or Japan [5,[11][12][13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared with previous cross-sectional studies of anemia prevalence in CKD, we observed higher proportions of severe CKD patients experiencing grade 2 or 3 anemia at any given point of time, likely due to the longitudinal nature of our study enabling us to identify incident anemia events. Our results corroborate earlier findings on the association between anemia and clinical outcomes in smaller and selected populations from the United States or Japan [5,[11][12][13].…”
Section: Discussionsupporting
confidence: 92%
“…Other possible causes of anemia include blood loss, iron deficiency, inflammation and accumulation of uremic toxins [4]. Prevalent anemia in CKD has been associated with cognitive impairment, sleep disturbances, CKD progression, cardiovascular disease and higher mortality in mostly older studies and in selected populations [5][6][7][8][9][10][11][12][13], whereas contemporary unselected population-based data on clinical outcomes associated with anemia are scarce. Treatment options for anemia include iron (oral and intravenous), erythropoietin stimulating agents (ESAs) and red blood cell transfusion to restore hemoglobin levels.…”
Section: Introductionmentioning
confidence: 99%
“…≥11.2 g/dL), the adjusted hemorrhagic stroke risk was increased 1.2-, 1.6-, and 2.3-fold for patients in Q3 (hemoglobin 10.6-11.1 g/dL), Q2 (9.8-10.5 g/dL), and Q1 (≤9.7 g/dL), respectively. 21 Richard A. Sherman…”
Section: Data From 77 607 Living Donor Transplants To Patients On Diamentioning
confidence: 99%
“…However, low hemoglobin levels did substantially increase the risk of hemorrhagic stroke . Compared to the quartile of patients with the highest hemoglobin levels (Q4; ≥11.2 g/dL), the adjusted hemorrhagic stroke risk was increased 1.2‐, 1.6‐, and 2.3‐fold for patients in Q3 (hemoglobin 10.6‐11.1 g/dL), Q2 (9.8‐10.5 g/dL), and Q1 (≤9.7 g/dL), respectively …”
mentioning
confidence: 96%
“…15 The Q-cohort study revealed that a low Hb level was reported to be associated with a high risk of haemorrhagic stroke, but not of ischaemic stroke. 16 Only sparse data were available on the prevalence of anaemia and anaemia monitoring for more than 1000 patients undergoing haemodialysis in Guangdong Province, China. Little is known about the relationship between different Hb levels and cardiocerebral vascular prognosis in the population of this region.…”
Section: Introductionmentioning
confidence: 99%